2020
DOI: 10.1177/1066480720961496
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Parenting Style and Parental Accommodations: The Moderating Role of Internalizing and Externalizing Symptomatology

Abstract: High parental involvement has been linked to positive outcomes; however, helicopter parenting may result in negative outcomes. The behaviors demonstrated by “helicopter parents” resemble parental accommodations, which are behavior modifications intended to alleviate their child’s distress. The current study examined the relation between helicopter parenting and parental accommodations, while also examining child internalizing and externalizing symptomatology as possible moderators. Parents ( N = 400) of childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
(89 reference statements)
0
12
0
Order By: Relevance
“…In general, studies examining HP frequently focused on university student population (Casillas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, studies examining HP frequently focused on university student population (Casillas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In general, studies examining HP frequently focused on university student population (Casillas et al, 2021). Helicopter parents who have college‐age children commonly supervise their children's assignments, choose the courses they participate in, get in touch with college presidents, deans, and academics, negotiate on the grade with the instructors, ask for an extension for their child, and even accompany their children to job expos and interviews (Locke et al, 2016; Vinson, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Helicopter parenting is accompanied by a series of negative consequences ( Casillas et al, 2021 ), including subjective and academic ill effects ( Schiffrin et al, 2014 ). In addition, research suggests that strong parenting beliefs do not help children engage in structured activities ( Schiffrin et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Casillas et al . [ 16 ] observed that more parental involvement has positive outcomes; however, helicopter parenting may lead to poor or negative outcomes.…”
Section: Discussionmentioning
confidence: 99%